Coffee and Alzheimer's Disease: Reviewing the Neuroprotective Effects of Bioactive Compounds - Katarzyna Madyniak; Piotr Ciecierski (Nicolaus Copernicus University in Toruń, 2024)
Alzheimer's disease (AD) is a common neurodegenerative disorder primarily managed with symptomatic treatments. Coffee, a popular beverage, contains bioactive compounds like caffeine, chlorogenic acid, quercetin, trigonelline, caffeic acid, and kaempferol, which may offer neuroprotective benefits. These compounds could potentially address AD-related pathologies such as amyloid-beta accumulation, tau hyperphosphorylation, oxidative stress, and inflammation. This review explores the neuroprotective potential of coffee's bioactive components in AD. Aim of the Study This study aims to review research on the neuroprotective effects of coffee and its bioactive compounds in Alzheimer's disease. It seeks to understand how these compounds may mitigate AD-related pathologies and their potential in preventive and therapeutic applications. The study also identifies knowledge gaps and suggests future research directions. Material and Methods We reviewed literature from PubMed, Google Scholar and other scientific sources using keywords: Alzheimer's disease, coffee, neuroprotective, caffeine, chlorogenic acid, quercetin, trigonelline, caffeic acid, and kaempferol. Conclusions Emerging evidence indicates that coffee's bioactive compounds may offer neuroprotective benefits against Alzheimer's disease. Compounds such as caffeine, chlorogenic acid, quercetin, trigonelline, caffeic acid, and kaempferol show potential in mitigating key AD pathologies. However, the current evidence is preliminary, and more research is needed to fully understand their cognitive benefits and mechanisms. Investigating these properties is particularly relevant given the aging global population and the age-related nature of AD.